Women Work and Values : contradictions in the prevailing nations and realities of women's lives in rural Bangladesh - Khan, Zarina Rahman (Dhaka : Centre for Social Studies, University of Dhaka, 1992)
Health and Population
Includes bibliographical reference
1999-09-27
Keywords: Females; Women Workers; Bangladesh